2017
DOI: 10.5603/nmr.2017.0004
|View full text |Cite
|
Sign up to set email alerts
|

MRI and 18F-FDG-PET/CT in a rare case of early (precursor) B-lymphoblastic leukaemia with bone involvement as initial manifestation

Abstract: A 4-year old girl presenting gait difficulty was referred for spine X-ray and Magnetic Resonance Imaging (MRI). MRI showed several diffuse hypointense signals in sacral and lumbar vertebrae. In order to exclude a possible lymphoproliferative disease a 18-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG-PET/CT) was requested. The PET/CT scan confirmed the MRI findings and demonstrated additional findings in the sternum. Therefore, a bone marrow biopsy was performed and a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…There is no consensus on the diagnostic and predictive value of PET/CT for intramedullary acute leukemia. Several papers reported that PET/CT incidentally detected acute lymphoblastic leukemia (ALL) (8)(9)(10)(11), and a few studies have reported the evaluation and predictive value of PET/CT in patients with leukemia (12,13). The prospective PETAML trial reported that the specificity of 18 F-FDG-PET/CT for diagnosis of extramedullary acute myeloid leukemia was 97%, despite hematological remission (14).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the diagnostic and predictive value of PET/CT for intramedullary acute leukemia. Several papers reported that PET/CT incidentally detected acute lymphoblastic leukemia (ALL) (8)(9)(10)(11), and a few studies have reported the evaluation and predictive value of PET/CT in patients with leukemia (12,13). The prospective PETAML trial reported that the specificity of 18 F-FDG-PET/CT for diagnosis of extramedullary acute myeloid leukemia was 97%, despite hematological remission (14).…”
Section: Discussionmentioning
confidence: 99%